2018
DOI: 10.1002/bjs.10920
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the diagnostic accuracy of ultrasound-guided fine-needle aspiration and core needle biopsy in diagnosing axillary lymph node metastasis

Abstract: US-CNB is a superior diagnostic technique to US-FNA for axillary staging in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 34 publications
(110 reference statements)
1
61
0
Order By: Relevance
“…[5][6][7] From these reports, CNB provided high sensitivity and low false-negative rate. [5][6][7] From these reports, CNB provided high sensitivity and low false-negative rate.…”
Section: Introductionmentioning
confidence: 90%
“…[5][6][7] From these reports, CNB provided high sensitivity and low false-negative rate. [5][6][7] From these reports, CNB provided high sensitivity and low false-negative rate.…”
Section: Introductionmentioning
confidence: 90%
“…A recent meta‐analysis assessed complication rates after US + CNB of morphologically atypical axillary lymph nodes . Combined data from five studies showed a postprocedure complication rate of 36/502 (7.1%), with pain being the most common complication described.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications included hematoma and bruising. No perinodal fibrosis was reported . Another study reviewed the operative notes and complications of US‐guided axillary lymph node 13‐gauge VAB and 14‐gauge CNB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations